1998
DOI: 10.1038/2023
|View full text |Cite
|
Sign up to set email alerts
|

A newly discovered class of human hematopoietic cells with SCID-repopulating activity

Abstract: The detection of primitive hematopoietic cells based on repopulation of immune-deficient mice is a powerful tool to characterize the human stem-cell compartment. Here, we identify a newly discovered human repopulating cell, distinct from previously identified repopulating cells, that initiates multilineage hematopoiesis in NOD/SCID mice. We call such cells CD34neg-SCID repopulating cells, or CD34neg-SRC. CD34neg-SRC are restricted to a Lin-CD34-CD38- population without detectable surface markers for multiple l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
444
1
6

Year Published

1999
1999
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 570 publications
(471 citation statements)
references
References 34 publications
20
444
1
6
Order By: Relevance
“…The absence of expression on these cells was not dependent on the epitope recognized by the CD150 mAb used in this study, because five other CD150 mAbs were tested and all yielded identical results (Table 4). This finding does not exclude the possibility that CD150 is expressed on a very small subset of CD133 − CD34 − HSCs [20]. Analysis of CD150 on cytokine-mobilized PBLs before CD133 magnetic selection showed that 1.64% of CD34 − CD45 + Lin − cells expressed CD150 (data not shown).…”
Section: Resultsmentioning
confidence: 94%
“…The absence of expression on these cells was not dependent on the epitope recognized by the CD150 mAb used in this study, because five other CD150 mAbs were tested and all yielded identical results (Table 4). This finding does not exclude the possibility that CD150 is expressed on a very small subset of CD133 − CD34 − HSCs [20]. Analysis of CD150 on cytokine-mobilized PBLs before CD133 magnetic selection showed that 1.64% of CD34 − CD45 + Lin − cells expressed CD150 (data not shown).…”
Section: Resultsmentioning
confidence: 94%
“…Recent reports have also suggested that human CD34 -cells in CB and BM cells contain in vivo hematopoietic repopulating cells in NOD/SCID mice [23] and in sheep [38]. These observations led us to study whether the fractions of CD34 -cells in CB may contain SRCs.…”
Section: Engraftment Of Cd34 -Cells From Human Cb Cells In Nod/scid Micementioning
confidence: 98%
“…However, the phenotype of SRCs was not elucidated in this study. More recently, using the same NOD/SCID xenograft system, they demonstrated that SRCs are also present in the CD34 -fraction of human CB cells [23].…”
Section: Introductionmentioning
confidence: 99%
“…The frequency of human and murine hematopoietic stem cells has been estimated to be 1/10 4 -10 5 bone marrow cells (Harrison et al, 1989;Sutherland et al, 1989;Harrison, 1993;Szilvassy and Hoffman, 1995;Bhatia et al, 1998;Abkowitz et al, 2002). The rarity of this population presented considerable impediments to isolation until recently.…”
Section: Methods Of Identifying Hematopoietic Stem and Progenitor Cellsmentioning
confidence: 99%